Analysis of Employee Wages in The Perspective of Maslahah (Study of Mangnguluang Laying Hen Farm, Kalumeme Village, Ujung Bulu District, Bulukumba Regency) - Mas’ud, Faiqah; Anwar, Nurfiah; Yunus, Ayu Ruqayyah (Jurnal Ar-Ribh, 2025)
Wage analysis is the process of reviewing or reviewing wage decisions or policies made by business actors to compensate their workers for the services provided. One of the analytical techniques used by ushul scholars to ensure that the laws (istinbat) whose problems are not expressly regulated in the Qur'an and Hadith is the maslahah point of view. This study aims to find out how the employee wage system is and how to review the perspective of the employee wage system in Mangnguluang Cattle, Tabuttu Kel. The type of research used is descriptive research, which describes the state of a thing or event that occurred both in the present and in the past. The information in this study was collected through observation and interviews. In this study, qualitative research techniques. The wage system at the Mangguluang Laying Hen Farm implements unilateral wage giving without a clear agreement between employees and management. In the perspective of maslahah, the practice of wages without an employment contract is not allowed because it is not in accordance with Islamic law. All employees said that the salary or wages they received were not enough to accommodate all the needs of daily life. Employees or employees' families have not been able to access higher education. While still united, single couples are able to save for marriage needs but not after marriage, and the same is true in an effort to have assets.